2007
DOI: 10.1093/hmg/ddm253
|View full text |Cite
|
Sign up to set email alerts
|

α7 nicotinic acetylcholine receptor mRNA expression and binding in postmortem human brain are associated with genetic variation in neuregulin 1

Abstract: Studies in cell culture and in animals suggest that neuregulin 1 (NRG1), a probable schizophrenia susceptibility gene, regulates the expression of the alpha7 nicotinic acetylcholine receptors (nAChRs). We hypothesized that schizophrenia-associated allelic variations within the NRG1 gene, via their effects on NRG1 isoform expression, would be associated with alterations in nAChR alpha7 receptor levels. We examined the effects of four disease-associated single-nucleotide polymorphisms (SNPs) in the 5' region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 73 publications
2
36
0
Order By: Relevance
“…Human brain specimens were processed, RNA was extracted, and quantitative RT-PCR (qRT-PCR) was performed using a paradigm described previously (Mathew et al, 2007). Species-specific probes and primer sets (Applied Biosystems) were used; for human NKCC1 (SLC12A2): Catalog No.…”
Section: Methodsmentioning
confidence: 99%
“…Human brain specimens were processed, RNA was extracted, and quantitative RT-PCR (qRT-PCR) was performed using a paradigm described previously (Mathew et al, 2007). Species-specific probes and primer sets (Applied Biosystems) were used; for human NKCC1 (SLC12A2): Catalog No.…”
Section: Methodsmentioning
confidence: 99%
“…There is extensive evidence linking genetic alterations of α7-nAChR to schizophrenia and attentional deficits (18,19), including alterations at the transcription level (20). Recent data have also shown that α7-nAChR expression depends on neuregulin, another molecule linked to schizophrenia (21), and that smoking in schizophrenia may be a form of self-medication, normalizing expression of α7-nAChRs (22). More recent studies have linked α7-nAChRs to autism (23), attention deficit hyperactivity disorder [ADHD (24)], and AD (25), suggesting that a variety of dlPFC disorders are linked to alterations in α7-nAChR signaling.…”
mentioning
confidence: 99%
“…The cholinergic receptors (e.g., α7 nicotinic acetylcholine receptor) known to be sensitive to NO toxicity were decreased in both the blood and cortex of patients with schizophrenia (Mathew et al 2007 ). Some neuropsychological tests performed in patients with schizophrenia as well as in healthy controls indicated that nNOS was associated with functions of the prefrontal cortex, including cognition.…”
Section: The Ionotropic Glutamate Receptors Nitric Oxide and Schizomentioning
confidence: 99%